ANTI-INFLAMMATORY ACTIVITY OF ALCOHOLIC AND AQUEOUS HEARTWOOD EXTRACTS OF BERBERIS ARISTATA DC - Singh, Vijender; Gunjan, .; Katiyar, Deepti (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective – To evaluate the anti-inflammatory activity of alcoholic and aqueous heartwood extracts of Berberis aristata DC. Method- The air dried coarsely powdered plant material (500 gm. each) was extracted with ethanol and distilled water for six hrs. Then the ethanolic extract was distilled off at low temperature under reduced pressure and water extract was completely air dried on water bath. Dried alcoholic and aqueous extracts were screened for the anti-inflammatory activity. Result- The ethanolic and aqueous extracts of Berberis aristata DC. heartwood exhibited significant anti-inflammatory activity with percent inhibition 33.40percent & 44.50percent at a dose of 25 mg/kg, p.o., and 52.20percent & 57.0percent at a dose of 50 mg/kg, p.o., respectively. Whereas standard drug, Indomethacin showed an inhibition of 64.80percent. Conclusion- The alcoholic and aqueous extract of Berberis aristata showed their maximum effect in 4th hour. Therefore, it can be concluded that both the extracts have potential to inhibit the serotonin, histamine & prostaglandins and can be used as a potent anti-inflammatory agent. Keywords- Berberis aristata, Indomethacin, Carageenan